2023
DOI: 10.3389/fnut.2023.1062817
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers associated with breastfeeding among mothers attending primary healthcare facilities in Mpumalanga, South Africa

Abstract: IntroductionDespite the health benefits of breastfeeding for both the mother and the child, early cessation of breastfeeding remains a public health problem in South Africa, attributed to contextual barriers and facilitators. Within the context of Mpumalanga province, which is characterized by low breastfeeding rates and high infant mortality rates in children under 5 years, we explored the facilitators and barriers to breastfeeding among mothers attending the three primary health facilities in Ermelo.MethodsU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…6,9 Family guidance and support were also identified as factors contributing to the success of EBF in the Mpumalanga region of South Africa. 16 This finding is not surprising compared to our survey results because the populations of Mpumalanga consist of Bantu people who share similar cultures to those in Gabon. Some factors regularly analysed in the literature, such as the number of prenatal consultations and the existence of breastfeeding preparation sessions, could not be analysed in our study due to the absence of uniform pregnancy follow-up logs; some diaries had pregnancy follow-up pages mentioning these sessions, while others did not, or the parents did not have them during the interviews.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…6,9 Family guidance and support were also identified as factors contributing to the success of EBF in the Mpumalanga region of South Africa. 16 This finding is not surprising compared to our survey results because the populations of Mpumalanga consist of Bantu people who share similar cultures to those in Gabon. Some factors regularly analysed in the literature, such as the number of prenatal consultations and the existence of breastfeeding preparation sessions, could not be analysed in our study due to the absence of uniform pregnancy follow-up logs; some diaries had pregnancy follow-up pages mentioning these sessions, while others did not, or the parents did not have them during the interviews.…”
Section: Discussionsupporting
confidence: 63%
“…Other surveys in India, Indonesia, and South Africa highlighted living in an urban area as a factor favouring EBF. 8,9,16,17 On closer reading of these results, the existence of medical structures encouraging mothers to breastfeed before and after birth also make a difference, as there were more "baby-friendly" structures in theses cities.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that although the majority of breastfeeding mothers were opposed to the use of traditional medicine or practices, their family elders proposed their use for the protection of their infants; participants from rural regions regularly reported using traditional medicine or practices [ 44 ]. Numerous studies have reported that women engage in complementary infant feeding practices because of cultural beliefs and family pressures [ 3 , 13 , 16 , 20 , 21 , 31 , 33 , 38 ]. The majority of African societies are unfamiliar with EBF because it contradicts their deeply held cultural beliefs and customs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sociocultural, economic, and healthcare system-related concerns are associated with insufficient lactation practices in South Africa. Social conditions, such as a lack of income, reliance on food purchases, young mothers’ emotions about breastfeeding, and cultural beliefs were the primary determinants of mothers’ breastfeeding behaviors [ 30 , 31 , 32 ]. The breastfeeding process also excludes fathers.…”
Section: Introductionmentioning
confidence: 99%